Development of a Test and Analysis Infrastructure for Sensors Bonded on Timepix3 ASIC - Shaker,Adib (2026)
Hybrid detectors, consisting of semiconductor sensors bonded to a readout Application-Specific Integrated Circuits (ASICs), are widely used for single-photon detection in photon science and high-energy physics. The Timepix3 readout chip provides precise Time-over-Threshold (ToT) and Time-of-Arrival (ToA) measurements, making it a valuable tool for sensor characterization. This thesis presents the design, implementation, and validation of a complete test and analysis infrastructure for the Timepix3 readout ASIC, targeting applications in synchrotron X-ray imaging, spectroscopy, and diffraction. The research stablished a complete hardware and software pipeline, integrating electrical and energy characterization of the bonded sensors with a custom data acquisition system. This infrastructure enabled I-V measurement, automated threshold scanning, precise energy calibration, and the implementation of a novel isolated-pixel analysis algorithm that significantly improves energy resolution by mitigating charge-sharing effects. Validation was conducted using an Fe-55 source and monochromatic X-ray beams at the NanoMAX and FemtoMAX beamlines at MAX IV. The system successfully characterized standard silicon sensors, demonstrating high linearity essential for spectroscopic accuracy, and provided proof-of-concept validation for wire-bonded Low-Gain Avalanche Diodes (LGADs) prototypes. These results confirm the infrastructure’s capability to support future high-speed imaging and energy-dispersive spectroscopy, providing a verified platform for the deployment of bump-bonded LGAD modules in next-generation photon counting experiments.
Keywords: Timepix3; Hybrid pixel detector; X-ray sensor characterization; Energy calibration; Data acquisition system; DAQ; ASIC readout; Katherine readout device